Training needs assessment with regard to individual needs of middle level managers (A comparative study of public and private sector banks) - Kumar, Rohit; Gill , Pushpinder Singh (Gyan Management Journal, 2011)
Individual analysis in the organization helps in making better decision making and effective problem solving skills by the employees. Through training and development, the employees become motivated and strive for achievement, growth, responsibility and advancement in their respective careers. This helps a person to handle stress, tension, frustration and conflict. Training provides information for improving leadership, knowledge, communication skills and attitudes. Increases job satisfaction and recognition. Individual analysis helps in moving a person towards personal goals while improving interpersonal skills. This also satisfies personal needs of a trainee. Provides trainee an opportunity for growth in his or her future.Analysis helps in developing a sense of learning. Individual analysis helps in assessing how well the individual employee is doing the job and determines which employee needs training and what kind of Training is required by the employee. Sources of information available for an individual analysis include: Performance evaluation, Performance problems, Observation, Work samples, Interviews, Attitude surveys, Checklists or training charts. This research has shown how assessment of individual training needs of middle level managers is done by themselves; it also determines the various functional and operational skills needed for proper effectiveness of banking operations. The study describes how public and private sector banks differ in their opinion regarding assessment of individual needs.
Keywords: Assessment; training; development; interpersonal skills; performance evaluation